Oral Manifestation in Pregnant Women in Sulaimaniyah City - A Hama Amin, Sonya; Mohamed Ahmed , Khadija (Diyala Journal of Medicine, 2023)
Background: Pregnancy is a physiological process during which a major hormonal change take place which leads to an imbalance in the oral environment and development of oral manifestation that can adversely affect mother’s health and the health of the unborn child. Objective: To assess the prevalence of the oral manifestation of pregnant women and to evaluate the correlation of these manifestations with the oral hygiene status. Patients and Methods: A total of 150 pregnant women were enrolled in this study on which a meticulous intraoral examination and evaluation of oral health status using oral hygiene index simplified (OHI-S) carried out. Results: The most involved age group was (21-25) years 38.00%. It was concluded that the most frequent oral finding was halitosis 67.33%, followed by dry mouth 59.33%, taste alteration 46%, pregnancy epulis 9.33%, candidiasis 7.33%, and ulceration 4%. In addition, pregnancy epulis and halitosis were significantly correlated with poor oral hygiene. Conclusion: Pregnancy is associated with oral manifestations; therefore, dentists should be aware of such manifestations and provide education regarding oral health status and maintenance of good oral hygiene during pregnancy